Combating Illicit Trafficking in Medical Products under International Law - Yaseen Abdul Khudhair , Assist. Prof. Dr. Zainab (Basra studies journal, 2026)
Illicit trafficking in medical products constitutes a serious threat to individual health and safety and poses significant challenges to international public health systems. This phenomenon deprives communities of essential medical resources, undermines public well-being, and weakens trust in healthcare institutions. It also disrupts the legitimate economy by causing financial losses to original manufacturers and damaging their reputation. Moreover, governments are deprived of public revenues and critical resources necessary for effective governance and anti-corruption efforts. Counterfeit medicines, as one of the most prevalent forms of illicit medical trafficking, represent a global health hazard that can lead to death and disability. The persistence of this crime is often linked to weak regulatory frameworks, inadequate enforcement mechanisms, and insufficient criminal penalties. Despite ongoing international efforts, the identification of competent law enforcement authorities and the effective exchange of real-time criminal data across borders remain major challenges. Therefore, strengthening international legal cooperation and harmonizing regulatory standards are essential components in combating this transnational crime.